2023
DOI: 10.1111/jpi.12850
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and evolutionary dissection of melatonin response signaling facilitates the regulation of plant growth and stress responses

Abstract: The expansion of gene families during evolution could generate functional diversity among their members to regulate plant growth and development. Melatonin, a phylogenetically ancient molecule, is vital for many aspects of a plant's life. Understanding the functional diversity of the molecular players involved in melatonin biosynthesis, signaling, and metabolism will facilitate the regulation of plant phenotypes. However, the molecular mechanism of melatonin response signaling elements in regulating this netwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 310 publications
0
9
0
Order By: Relevance
“…76,77,281,282 Several enzymes are involved in MEL biosynthesis and metabolism (see Figure 1) and the functional characterization of genes encoding those enzymes relating to MEL biosynthesis and metabolism showed a diverse role of MEL in regulating plant growth and SG. 282 For instance, the ectopic expression of SNAT gene in rice increased seed width and length by regulating the gene expression of GRAIN INCOMPLETE FILLING-1 (GIF1) and GRAIN WIDTH-2 (GW2) and MEL accumulation in seeds. 283 Likewise, overexpression of VvSNAT gene in Arabidopsis resulted in higher SG rate and root and shoot length associated with better ROS scavenging and higher MEL accumulation.…”
Section: Functional Role Of Mel Related Genes In Regulating Sgmentioning
confidence: 99%
See 1 more Smart Citation
“…76,77,281,282 Several enzymes are involved in MEL biosynthesis and metabolism (see Figure 1) and the functional characterization of genes encoding those enzymes relating to MEL biosynthesis and metabolism showed a diverse role of MEL in regulating plant growth and SG. 282 For instance, the ectopic expression of SNAT gene in rice increased seed width and length by regulating the gene expression of GRAIN INCOMPLETE FILLING-1 (GIF1) and GRAIN WIDTH-2 (GW2) and MEL accumulation in seeds. 283 Likewise, overexpression of VvSNAT gene in Arabidopsis resulted in higher SG rate and root and shoot length associated with better ROS scavenging and higher MEL accumulation.…”
Section: Functional Role Of Mel Related Genes In Regulating Sgmentioning
confidence: 99%
“…The regulatory role of exogenously applied MEL in mediating SG under abiotic stresses is subjected to the MEL dose dependency, stress exposure time and seed quality 76,77,281,282 . Several enzymes are involved in MEL biosynthesis and metabolism (see Figure 1) and the functional characterization of genes encoding those enzymes relating to MEL biosynthesis and metabolism showed a diverse role of MEL in regulating plant growth and SG 282 .…”
Section: Functional Role Of Mel Related Genes In Regulating Sgmentioning
confidence: 99%
“…In plants, melatonin was discovered only in 1995 [ 11 , 13 ]. Melatonin is a multi-functional molecule [ 17 , 18 , 19 ]. Both melatonin itself and its metabolic products (cyclic 3-hydroxymelatonin, N1-acetyl-N2-formyl-5-methoxykynuramine, N1-acetyl-5-methoxykynuramine, 6-hydroxymelatonin and 2-hydroxymelatonin) act as effective antioxidants, reducing the content of ROS or reactive nitrogen species (RNS), which leads to a decrease in the intensity of lipid peroxidation [ 11 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Melatonin acts as a signaling molecule, affecting gene expression through interactions with specific melatonin receptors and modulating the activity of transcription factors involved in stress‐responsive pathways. For instance, NAC transcription factor genes are involved in the resistance to plant abiotic stress regulated by melatonin (Gao et al, 2023). As an antioxidant and activator of the plant's enzymatic and non‐enzymatic antioxidant system, it also plays an essential role in redox homeostasis in plant cells under stressful conditions (Rehaman et al, 2021; Tiwari et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The biosynthesis of melatonin in plants involves four enzymatic steps catalyzed by tryptophan decarboxylase (TDC), tryptamine 5‐hydroxylase (T5H), serotonin N‐acetyltransferase (SNAT), N‐acetylserotonin methyltransferase (ASMT), and caffeic acid O‐methyltransferase (COMT; Back, 2021). Gene expression studies have revealed that the expression of melatonin biosynthesis genes is induced under abiotic stress conditions, leading to increased melatonin production (Gao et al, 2023). Through gene knockout or overexpression experiments, researchers have demonstrated the impact of these genes on drought tolerance.…”
Section: Introductionmentioning
confidence: 99%